Unraveling persistent dyspnea after mild COVID: insights from a case series on hyperventilation provocation tests - Ritter, Ophélie; Noureddine, Sofia; Laurent, Lucie; Roux, Pauline; Westeel, Virginie; Barnig, Cindy (Frontiers in Physiology, 2024)
Dyspnea is a common yet poorly understood symptom of long COVID, affecting many patients. This brief report examines the role of dysfunctional breathing in persistent dyspnea among patients with mild post-COVID-19 using hyperventilation provocation tests (HVPT). In this case series, six patients with unexplained dyspnea and normal cardiopulmonary function underwent HVPT. Despite normal exercise testing results, all patients exhibited delayed PETCO2 recovery, indicative of a hyperventilation pattern consistent with chronic hyperventilation syndrome, without typical symptomatic manifestations. These findings suggest underlying post-COVID respiratory dysregulation, emphasizing the importance of targeted diagnostic and therapeutic approaches for persistent respiratory symptoms in long COVID patients.